2023
DOI: 10.1039/d3cs00251a
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation behaviour of pyrene-based luminescent materials, from molecular design and optical properties to application

Xing Feng,
Xiaohui Wang,
Carl Redshaw
et al.

Abstract: This review not only highlights the progress of the emission and electronic behaviour of new pyrene-based luminescence molecules in the aggregated state, but also provides a new perspective for understanding the luminescence mechanism and optoelectronic properties of pyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 265 publications
0
37
0
Order By: Relevance
“…26−29 Generally, pyrene-based emitters with AIE properties exhibit weak emission in dilute solution but could boost the fluorescence brightness in the aggregated state, which eventually has helped to solve the above-mentioned fluorescence quenching issue. 17,22 In light of the generally acknowledged working mechanism of AIE, the basic design principle of AIEgens lies in the distorted architectures and twisted molecular rotors. Such a design can lead to the efficient constraint of the intermolecular π−π stacking interactions and a resulting high fluorescence quantum yield (QY) in the aggregated state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26−29 Generally, pyrene-based emitters with AIE properties exhibit weak emission in dilute solution but could boost the fluorescence brightness in the aggregated state, which eventually has helped to solve the above-mentioned fluorescence quenching issue. 17,22 In light of the generally acknowledged working mechanism of AIE, the basic design principle of AIEgens lies in the distorted architectures and twisted molecular rotors. Such a design can lead to the efficient constraint of the intermolecular π−π stacking interactions and a resulting high fluorescence quantum yield (QY) in the aggregated state.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) featuring large π-conjugated architectures are a significant category of functional materials by virtue of their remarkable photophysical, electrical, and mechanical performances and have been successfully applied in diverse fields, ranging from organic field-effect transistors, , organic photovoltaic cells, and organic/quantum dot light-emitting diodes to fluorescence sensors. As one of the extensively used and representative families of PAHs, pyrenes are chemically stable and contain four integrated benzene rings with extended π-electron delocalization . The unique flat aromatic scaffold endows pyrenes with salient properties, such as deep blue fluorescence, high charge carrier mobility, and prominent hole injection capacity, making them excellent candidates for organic optoelectronic materials, chemosensors, and bioimaging applications. However, the fluorescence output of pyrene aggregates is usually inferior to what can be achieved in their respective solutions, and this hampers their potential high-technological application in fluorescence-relevant areas. , The weakened emission in the aggregated state may be attributed to the facile generation of detrimental substances such as excimers, given that the planar structure of pyrene tends to undergo intense intermolecular π–π stacking interactions once aggregated. Therefore, exploring feasible approaches to promote the aggregate-state fluorescence of pyrenes is of great interest when trying to facilitate their latent applications in organic optoelectronics and other extensive scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrene 20,21 is a typical four phenyl-fused polycyclic aromatic hydrocarbon compound, which displays intense blue fluorescence in solution ( λ em = 372 nm, Φ f = 0.64). 22,23 However, pyrene prefers to form a dimer at high concentration, resulting in a red-shifted emission with fluorescence quenching. 24 Due to its high luminescence efficiency, ease of chemical modification, and low cost, it is often used to design and synthesize fluorescent probe molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Conversely, discrete π stacking, such as dimer structure, can enhance luminescence due to the suppression of non-radiative energy transfer decay. [20][21][22][23] As a typical sample, pyrene is proved to have the characteristic of dimer-induced emission enhancement in recent years. For example, Talukder et al synthesized an 8hydroxyquinoline pyrene derivative and found that metal was capable of promoting the formation of pyrene dimer structure through coordination effect, thus leading to an emission enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Long range π stacking usually suppresses the luminescence efficiency because of the low‐energy trap states [19] . Conversely, discrete π stacking, such as dimer structure, can enhance luminescence due to the suppression of non‐radiative energy transfer decay [20–23] . As a typical sample, pyrene is proved to have the characteristic of dimer‐induced emission enhancement in recent years.…”
Section: Introductionmentioning
confidence: 99%